Energy Sovereignty and Structural Dependence: Towards a Congolese Doctrine of Energy Transition - LUNDA NGANDU , Guy (Revue Internationale du Chercheur, 2025)
Abstract The Democratic Republic of Congo (DRC), endowed with more than 60% of Africa’s hydroelectric potential, paradoxically remains one of the most energy-dependent countries, with an electrification rate of less than 20% of the population. This paradox reflects structural dependence, both technological and financial, which undermines the emergence of national energy sovereignty. This article provides a political-strategic reading of the Congolese energy transition through the theoretical framework of dependency theory and political ecology. The adopted methodology relies on a qualitative documentary analysis of 30 sources (official reports, public policies, academic works, and statistical data from 2010 to 2025) and a comparative perspective with Morocco, Brazil, and South Africa. The findings highlight fragmented governance, strong reliance on external financing, and weak industrial valorization of local resources. The article advocates for the development of a Congolese doctrine of energy transition, based on energy justice, techno-industrial sovereignty, and proactive green diplomacy. The sample size mobilized consists of 30 documentary sources, complemented by a comparative analytical grid applied to three foreign case studies.